Methane transport and sources in an Arctic deep-water cold seep offshore NW Svalbard (Vestnesa Ridge, 79°N) - Sauer, Simone; Hong, Wei-Li; Yao, Haoyi; Lepland, Aivo; Klug, Martin; Eichinger, Florian; Himmler, Tobias; Cremiere, Antoine; Panieri, Giuliana; Schubert, Carsten J.; Knies, Jochen (Deep Sea Research Part I: Oceanographic Research Papers, 2020)
We investigate the uppermost 60 cm of sediment in active pockmarks of a deep-water methane seep site from Vestnesa Ridge offshore NW Svalbard. Using video guided core sampling with a remotely operated vehicle we collected push cores directly from bacterial mats within two active pockmarks, Lunde and Lomvi. Pore water analyses show very shallow sulphate methane transition zones and transport-reaction modelling suggests a considerable amount of dissolved methane passing through the sediment water interface due to upwards advection of an aqueous fluid not previously reported from Vestnesa Ridge. In addition, we show that the amount of methane that bypasses the benthic methane filter greatly increases with higher aqueous fluid advection rate. Recent changes in methane flux are evident from lipid biomarker, seep carbonate, and δ13C-organic carbon profiles in both pockmarks. Hydrocarbons at this cold seep site are supplied both by deep thermogenic sources from below the gas hydrate stability zone but also to a significant degree by microbial methanogenesis which dominates the signature in our shallow sediment cores with δ13C–CH4 values as low as −77‰.